2016
DOI: 10.1002/chem.201600620
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions Play an Essential Catalytic Role in the Mechanism of Ketol–Acid Reductoisomerase

Abstract: Ketol-acid reductoisomerase (KARI) is a Mg(2+) -dependent enzyme in the branched-chain amino acid biosynthesis pathway. It catalyses a complex two-part reaction: an alkyl migration followed by a NADPH-dependent reduction. Both reactions occur within the one active site, but in particular, the mechanism of the isomerisation step is poorly understood. Here, using a combination of kinetic, thermodynamic and spectroscopic techniques, the reaction mechanisms of both Escherichia coli and rice KARI have been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 48 publications
4
43
0
Order By: Relevance
“…KARI is a bi‐functional enzyme catalyzing an isomerization reaction and an NAD(P)H‐mediated reduction. The enzyme has a strict requirement for Mg 2+ ions . Crystal structures of KARIs from different organisms have shown that both cofactors are located at the interface between the N‐ and C‐terminal domains of the enzyme .…”
Section: Introductionmentioning
confidence: 99%
“…KARI is a bi‐functional enzyme catalyzing an isomerization reaction and an NAD(P)H‐mediated reduction. The enzyme has a strict requirement for Mg 2+ ions . Crystal structures of KARIs from different organisms have shown that both cofactors are located at the interface between the N‐ and C‐terminal domains of the enzyme .…”
Section: Introductionmentioning
confidence: 99%
“…This includes all DNA and RNA polymerases, helicases, nucleases, ligases, as well as ATP and GTP kinases and beyond. The method may be applied to studying enzymes that are not involved in nucleotide and nucleic acid metabolism, for example, (1) GalNAc:polypeptide GalNAc-transferases (GalNAc-Ts), which catalyze the Mg 2+ -dependent transfer of GalNAc from UDP-GalNAc to a serine or threonine residue in the first step of mucin O-linked glycosylation (Bennett et al , 2012), (2) Ketol-Acid Reductoisomerases (KARI), which require two Mg 2+ ions for the isomerization step in branched amino acid synthesis (Tadrowski et al , 2016), and (3) the radical SAM enzyme QueE, which utilizes Mg 2+ for radical-mediated ring contraction (Dowling et al , 2014). …”
Section: Applications and Future Prospectsmentioning
confidence: 99%
“…The metal ion affinities, determined by ITC, are similar to those of the well-characterised antibiotic-degrading MBL AIM-1 (72) (see also Chapter 5) and cyclic nucleotide diesterases, (257) but significantly weaker than those recorded for phosphotriesterases. (232) To date the in vivo metal ion composition of CpsB remains obscure, but Mn 2+ appears to be the most likely candidate, based on optimal catalytic performance combined with bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…The excess of Co 2+ was removed and fitted to a minimum number of Gaussian peaks to achieve the final composite spectrum using GRAMS AI software package. The data were analysed as described elsewhere (22,(218)(219)(220)(229)(230)(231)(232) .…”
Section: Magnetic Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation